Macro-regional strategies as a catalyst for the further development of the European multi-level governance system? - Raymond Saller (Cross-border spatial development in Bavaria: Dynamics in cooperation - Potentials of integration, 2022)
Since the establishment of the partnership principle within EU regional policy in 1988, the role of cities in the European multi-level governance system has been progressively strengthened. Today, the cities of Europe are central actors with key functions in the implementation of EU regional policy. In parallel to the associated cross-border cooperation, the explicit recognition of local and regional self-government in the European basic treaties (Treaty of Lisbon, Pact of Amsterdam) politically strengthened the role of cities in the European multi-level governance system. This made it officially possible for European municipalities to cooperate with the European Commission and representatives of member states to draw up strategic position papers for future legislative initiatives. At the same time the establishment of macro-regions introduced a framework for the sectoral and geographical adaptation of policies to suit the regions in question. A key role in cross-border cooperation was thus assigned to the cities in the macro-regions. If European cities actively pursue these opportunities they have a chance to establish themselves as the fourth level in the European multi-level governance system and to strengthen their position within the national states and the European institutional framework. The adaptation of intra-state structures is seen as the most important precondition for the municipalities to be able to better express their interests as actors in the political multi-level governance system and thus to gain more influence in the EU. The City of Munich provides an example of how urban policy is, however, often slow to grasp the opportunities offered by the Urban Agenda and macro-regional strategies for European cities.
urn:nbn:de:0156-41580906; hdl:10419/253270; https://econpapers.repec.org/RePEc:zbw:arlabe:34
Keywords: 710; Macro-regional strategy; cross-border cooperation; EU regional policy; role of the cities; Urban Agenda; Munich; Europe of the cities